Multidimensional transition fronts for Fisher–KPP reactions. (8th February 2019) - Alwan, Amir; Han, Zonglin; Lin, Jessica; Tao, Zijian; Zlatoš, Andrej
Abstract: We study entire solutions to homogeneous reaction–diffusion equations in several dimensions with Fisher–KPP reactions. Any entire solution is known to satisfy and we consider here those satisfying When is and concave, our main result provides an almost complete characterization of transition fronts as well as transition solutions with bounded width within this class of solutions.